Find your why a practical guide for discovering purpose for you and your team - Simon Sinek (United Kingdom Penguin, 2017)
Start With Why has led millions of readers to rethink everything they do ? in their personal lives, their careers and their organizations.
Keywords: Attitude (Psychology)